Sacré Graal ! et le détournement cinématographique - Justine Breton (Perspectives Médiévales)
This paper focuses on narrative and aesthetic perspectives in the movie Monty Python and the Holy Grail, by studying the connections and divergences between Terry Gilliam’s cut-out animation sequences and their medieval inspirations in texts and illuminations. Text and image associated with an Arthurian tradition are directly incorporated within the movie, and help structure it through both didactic and farcical interludes. Medieval imagery is animated, shaken up or sometimes put at risk, in order to serve the numerous comical processes used in the movie. Following the same principle, medieval literary points of reference are mentioned to accompany the story and take part in the general shock of narrative and aesthetic codes inherent of Monty Python’s sense of humour.